Does the effectiveness of mutual aid depend on compatibility with treatment philosophies offered at residential rehabilitation services?. (April 2020) - Best, D.; Manning, V.; Allsop, S.; Lubman, D.I.
Highlights: Mutual aid attendance did not differ between TC and non-TC clients. SMART Recovery (non-12 step) attendance was higher among TC compared to non-TC residential treatments. Mutual aid attendance improved substance use outcomes for non-TC clients only. Abstract: Background: Residential rehabilitation treatment (including both Therapeutic Communities (TC) and non-TC rehabs) is a key component of service delivery for people seeking treatment for substance use disorders in Australia and globally. While mutual aid is often associated with better long-term outcomes, there is little evidence about whether inconsistencies between residential rehabilitation philosophies and particular types of mutual aid influence subsequent engagement and treatment outcomes. Objective: To assess the uptake of mutual aid groups (12-step and other) on individuals leaving TC (n = 58) or non-TC (n = 78) residential treatment, and measure its impact on substance use outcomes. Methods: Using secondary analysis of existing data, the current paper reports on 12-month outcomes from a prospective cohort study of 230 individuals entering specialist alcohol and other drug residential rehabilitation treatment in two Australian states. Results: Participants who attended TC settings were more likely to attend non-spiritual mutual aid groups (i.e., SMART Recovery) than non-TC residents. Engaging in mutual aid groups was associated with significantly improved outcomes for the non-TC residents only, where it significantly predicted abstinence (OR = 5.8, CI = 1.5–18.46) and reduced frequency of use of participants' primary drug of concern (OR = 8.6, CI = 2.6–28.6). Conclusions/Importance: Although 12-step is the most readily available and accessible form of mutual aid in Australia and benefited those attending non-TC residential rehabilitation, individuals exiting a TC program (whether they have completed treatment or not) may benefit from other forms of post-treatment recovery support, including alternative forms of peer-based support. The findings suggest treatment outcomes may be enhanced when the philosophies of residential treatment and post-discharge mutual aid are more compatible.